Bourne on Company Law - Nicholas Bourne (New York Routledge, 2016)
An ideal introductory textbook, Bourne on Company Law offers a succinct overview of the fundamental areas covered in LLB and GDL courses. The text is clear and easy to follow, being presented in short, sub-headed sections for ease of navigation, and is thoroughly cross-referenced to highlight connections across topics.
Keywords: Corporation law; Law; Company law; (ASB-2400) Law for Business